(untitled) (Ustozlar uchun, 2026)
This article presents a linguo-cultural analysis of Italian proverbs with antonymic correlations. Proverbs are viewed as a reflection of the people’s worldview, values, and life experience, through which the Italian national mentality and social principles are revealed. The study examines the semantic, stylistic, and cultural functions of proverbs formed on the basis of antonymic relations. Some Italian proverbs are compared with their Uzbek equivalents to identify semantic similarities and differences. As a result, it is demonstrated that antonymic correlation serves as an important means of expressing life philosophy, diligence, wisdom, and honesty in Italian proverbs. The findings of this research are significant for studying Italian phraseological units, interpreting their cultural meanings in translation, and effectively applying them in intercultural communication.